Revenge or collusion? An experiment on payoff subtraction and addition in team contests - Jiaxin Yu; Wanjun Zheng (PLoS ONE, 2025)
Group competition is prevalent in contemporary society. In this paper, we focus on the effects of payoff subtraction (revenge) and payoff addition (collusion) on expenditures in team competitions. Although theory predicts that the equilibrium of aggregate team contributions does not change, we find that competitive expenditures are indeed affected. Our results indicate that (1) embedding the payoff subtractions that target either the top investor or the entire team significantly reduces the contest expenditures of the targeted group; (2) targeting the top investor with conditional payoff subtractions (depending on relative expenses) leads to a slight reduction in total expenditures across both competing parties; and (3) if the primary objective is to reduce competitive expenditures, either to lower the rival group’s expenditures or to lower that of both sides, payoff additions of equal magnitude may be less effective than payoff subtractions. These findings provide valuable insights into potential mechanisms for reducing competitive resource waste.